The influence of the ketogenic diet on the therapy of type 2 diabetes. A literature review - Madej, Aleksandra; Senat, Hanna; Grabowska, Patrycja; Bolla, Patrycja; Senat, Aleksandra; Marczyńska, Zuzanna; Dorochowicz, Mateusz (Journal of Education, Health and Sport, 2024)
INTRODUCTION: Diabetes mellitus type 2 (DM2) is a widespread and chronic disorder with high mortality and associated morbidity rates worldwide. DM2 individuals are more susceptible to developing heart disease, cardiovascular disease, diabetic neuropathy, and several other related complications, which are major causes of diabetes related death. New therapies and possibilities for the treatment of the diabetes are constantly being searched for, among which the ketogenic diet is increasingly becoming popular. There are studies being conducted all worldwide on the effects of this diet on the treatment of diabetes. PURPOSE: The aim of the study is to present the current state of knowledge about the influence of the ketogenic diet on the therapy of type 2 diabetes. MATERIALS AND METHOD: The available literature in PubMed was reviewed to write the article, using the keywords ,,ketogenic diet”, ,,diabetes mellitus”, ,,ketogenic diet diabetes”, ,,diabetes nutrition”. CONCLUSION: A ketogenic diet has notable advantages on body weight and glycemic control, as well as on the enhancement of lipid profiles in overweight DM2 patients. This diet can decrease body weight, waist circumference, HbA1c, and triglycerides, and increase HDL levels. In addition, the ketogenic diet may have further benefits in improving body composition to attenuate the onset and progress of DM2 bz reducing body weight, lowering glycemic levels, and enhancing lipid profiles. More studies are needed in the future to support and even confirm the links between the ketogenic diet and patienst suffering from DM2.